Assessment Of Validity And Reliability Of Team STEPPS Teamwork Attitudes Questionnaire (T-TAQ) In Iran - Minoo Najafi; Fatemeh Keshmiri; Maryam Najafi; Mandana Shirazi (Tehran University of Medical Sciences, 2014)
Background and Aim: Collaboration within and between healthcare teams facilitates effective healthcare provision. Fundamental strategies in effective healthcare services focus on collaboration and teamwork. This study was an attempt to assess reliability and validity of Team STEPPS Teamwork Attitudes Questionnaire (T-TAQ) in Iranian context. Materials and Methods: This cross-sectional survey was conducted in Iran in 2012. Delphi method was applied and the questionnaire was submitted to 11 experts in 2 rounds to determine its face and content validity. Besides, it was translated and back translated to determine external validity. To estimate the reliability of the instrument, test-retest method was used. A sample of 67 medical and nursing senior students was stratified from Tehran University of Medical Sciences (TUMS). T-TAQ is a questionnaire having 30 questions in 5 themes. The obtained data were analyzed by SPSS13. Results: The content, face and external validity of the tool were approved by Iranian experts. Meanwhile, applying Cronbach's alpha, total reliability was estimated to be 0.80; moreover, the ICC turned out to be 0.8. Conclusion : Since the validity and reliability of this instrument are confirmed in an Iranian context, it can be used to measure attitude regarding teamwork in this context.